2016
DOI: 10.1111/hcre.12100
|View full text |Cite
|
Sign up to set email alerts
|

Beauty is Good: The Appearance Culture, the Internalization of Appearance Ideals, and Dysfunctional Appearance Beliefs Among Tweens

Abstract: Dysfunctional appearance beliefs have been identified as important risk factors in the development of body dissatisfaction and disordered eating behaviors among early adolescents. The current two‐wave study among 10–14‐year‐olds (N = 1,597, Mage = 11.25, SD = 1.05) aimed to delineate factors that contribute to the endorsement of such beliefs. Results showed that tweens discussed appearance‐related topics with their friends more often when they frequently watched tween television programs (all time 1). Both med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 59 publications
1
29
0
5
Order By: Relevance
“…This reasoning is in line with Engeln-Maddox's (2006) suggestion that women internalize appearance ideals because they believe it will bring about various rewards. Recently, Trekels and Eggermont (2016) confirmed these assumptions and showed that early adolescents were more likely to internalize appearance ideals if they believed that compliance with those ideals is rewarded.…”
Section: Explanatory Mechanismmentioning
confidence: 85%
See 1 more Smart Citation
“…This reasoning is in line with Engeln-Maddox's (2006) suggestion that women internalize appearance ideals because they believe it will bring about various rewards. Recently, Trekels and Eggermont (2016) confirmed these assumptions and showed that early adolescents were more likely to internalize appearance ideals if they believed that compliance with those ideals is rewarded.…”
Section: Explanatory Mechanismmentioning
confidence: 85%
“…Prior research has related exposure to sexualizing media messages to adolescents' cognitive preoccupation with outward appearance. Specifically, media exposure has been related to girls' and boys' self-objectification (i.e., valuing body appearance over body competence ;Vandenbosch & Eggermont, 2012), dysfunctional appearance beliefs (i.e., equating self-worth with appearance; Trekels & Eggermont, 2016), and anxiety to be judged and rejected based on their appearance (e.g., Trekels & Eggermont, 2017a). Studies have further shown that young girls may accept a narrow and sexualizing view on girls and women as part of their own identity (e.g., McKenney & Bigler, 2014a).…”
Section: Sexualizing Appearance Behaviors Among Youthmentioning
confidence: 99%
“…In extreme cases, reports show that a number of teenage girls go as far as posting nude 'selfies' in order to attract attention (Mascheroni et al, 2015). The tendency to internalise standards of beauty and self-objectify is thus influenced by perceived potential benefits such as popularity, and leads to attempts to emulate behaviours seen as most rewarding (Trekels et al, 2018;Trekels & Eggermont 2016;Mascheroni et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Research has explored the impact of watching gender-stereotypes and sexualized bodies on both boys and girls. For example, research has shown that children internalize information about bodies, sexualize and objectify themselves and others based on media exposure (Fredrickson & Roberts, 1997;Trekels & Eggermont, 2017). These kinds of beliefs are associated with lower expectations of girls and women's capabilities, and negative mental health outcomes (Grabe & Hyde, 2009;Tiggemann & Slater, 2015).…”
Section: Learning From Televisionmentioning
confidence: 99%